Synaptopodin is required for efficient intercellular spread by bacterial pathogens - Vickery, Jenna M; Toperzer, Jody D; Raab, Julie E; Hamilton, Desmond J; Harju, Tucker B; Huynh, Thao N; Zhou, Liheng; Lenz, Laurel L; Colgan, Sean P; Russo, Brian C (bioRxiv, 2024)
For many intracellular pathogens, their virulence depends on an ability to spread between cells of an epithelial layer. For intercellular spread to occur, these pathogens deform the plasma membrane into a protrusion structure that is engulfed by the neighboring cell. Although the polymerization of actin is essential for spread, how these pathogens manipulate the actin cytoskeleton in a manner that enables protrusion formation is still incompletely understood. Here, we show that butyrate responsive pathways promote intercellular spread by Shigella flexneri. We identify the mammalian actin binding protein synaptopodin, a butyrate responsive gene, as required for efficient intercellular spread of S. flexneri and Listeria monocytogenes. We show synaptopodin enhances the recruitment of actin to bacteria and stabilizes the actin tail. We show that, for S. flexneri, synaptopodin presence enables protrusions to form and to resolve at a greater rate, indicating that greater stability of the actin tail enables the bacteria to push against the membrane with greater force. We demonstrate that synaptopodin recruitment around bacteria requires the bacterial protein IcsA, and we show that this recruitment is further enhanced in a type 3 secretion system dependent manner. These data establish synaptopodin as required for intracellular bacteria to stabilize the actin cytoskeleton in a manner that enables efficient protrusion formation and identify for the first time that synaptopodin contributes to bacterial pathogenesis.Competing Interest StatementThe authors have declared no competing interest.Footnotes* We provide additional data and clarify text.